Cognitive development of imitation of intransitive gestures: an analysis of hand and finger errors. Issue 6 (18th August 2022) - Lesourd, Mathieu; Rey, Amandine E.
ABSTRACT: The dual-route model proposes that imitation of meaningful gestures relies on a lexical route whereas imitation of meaningless gestures relies on a sub-lexical route. The aim of the present study was to investigate the development of imitation of intransitive meaningful and meaningless gestures in children from 6 to 9 years old by exploring hand and finger errors. Despite lower performance, children showed similar patterns than adults with better imitation of meaningful compared to meaningless gestures. Concerning body part errors, children made more errors than adults. Moreover, children produced more hand errors than adults for meaningful gestures whereas they were no difference for meaningless gestures. These results suggest that the two routes are present but are still maturing. Moreover, several specific and non-specific factors may have impacted imitation skills. Further studies are needed to disentangle the role of these factors in imitation of intransitive gestures during development from childhood to adulthood.